Curfew Limits and Street Children: Analysis of Child Protection Policies in the Context of the SDGs - Gea, Lidia Kando Br; Nurlaily, Nurlaily; Tan, Winsherly (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The existence of street children basically shows problems in efforts to implement SDGs, especially the existence of street children roaming around at night. The lack of supervision and the vulnerability of various forms of crime place these children in a position that is vulnerable to various dangers, which gives rise to the urgency of handling measures that can accurately respond to this challenge. The objective of this research is to analyze the effectiveness of curfew policies in protecting street children and to assess their alignment with the SDGs targets related to child protection and social welfare. Using normative legal research methods, the research aims to analyze problems related to the presence of street children at night, using the SDGs perspective as the main reference. The analysis found that efforts to remove children from street life can be hampered by a number of complex social factors, which the existing legal framework cannot yet address. Therefore, this research proposes a policy model for limiting curfews by combining elements from several existing laws and regulations, which can be used to prevent street children's activities at night, increase child protection, as well as identify the potential for exploitation that could occur. endanger street children, by linking the role of parents. This policy model is expected to enhance child protection efforts and assist in removing children from street life, as a means of fulfilling the SDGs. The limitation of this research lies in the normative nature of the findings, necessitating further qualitative testing through various forms of effectiveness studies, particularly regarding the existing regulations and those to be incorporated into the policy model framework. [Keberadaan anak jalanan pada dasarnya menunjukkan permasalahan dalam upaya penerapan SDGs, khususnya keberadaan anak jalanan yang berkeliaran di malam hari. Minimnya pengawasan dan rawannya berbagai bentuk tindak kejahatan menempatkan anak-anak ini di dalam posisi yang rentan terhadap berbagai bahaya, yang menimbulkan urgensi penanganan yang dapat dengan akurat menjawab tantangan ini. Tujuan penelitian ini adalah untuk menganalisis efektivitas kebijakan batasan jam malam dalam melindungi anak jalanan, serta mengkaji kesesuaiannya dengan target SDGs terkait perlindungan anak dan kesejahteraan sosial. Dengan menggunakan metode penelitian hukum normatif, penelitian bertujuan menganalisis permasalahan yang berkaitan dengan keberadaan anak jalanan di malam hari, dengan menggunakan perspektif SDGs sebagai acuan utama. Analisis menemukan bahwa upaya mengeluarkan anak-anak dari kehidupan jalanan dapat dihalang oleh beberapa faktor sosial yang kompleks, yang belum mampu dijangkau oleh kerangka hukum yang berlaku. Maka dari itu, penelitian ini mengusulkan model kebijakan batasan jam malam dengan menggabungkan unsur-unsur dari beberapa peraturan perundang-undangan yang sudah ada, yang dapat digunakan untuk mencegah aktivitas anak jalanan di malam hari, meningkatkan perlindungan anak, sekaligus mengidentifikasi potensi terjadinya eksploitasi yang dapat membahayakan anak jalanan, dengan mengaitkan peran orang tua. Model kebijakan ini diharapkan dapat meningkatkan upaya perlindungan anak dan mengeluarkan mereka dari kehidupan di jalanan, sebagai bentuk pemenuhan SDGs. Limitasi dari penelitian adalah temuan yang didapat dari analisis sepenuhnya bersifat normatif, sehingga diperlukan pengujian secara kualitatif melalui berbagai bentuk studi efektivitas, khususnya mengenai kebijakan pengaturan-pengaturan yang sudah ada dan akan dimasukkan ke dalam konstruksi model kebijakan].